Tackling tuberculosis: insights from an international TB Summit in London - Maitra, Arundhati; Danquah, Cynthia Amaning; Scotti, Francesca; Howard, Tracey K; Tengku Mohd. Kamil, Tengku Karmila; Bhakta, Sanjib (Taylor & Francis Group, 2015)
Tuberculosis (TB) poses a grave predicament to the world as it is not merely a scientific challenge but a socio-economic burden as well. A prime cause of mortality in human due to an infectious disease; the malady and its cause, Mycobacterium tuberculosis have remained an enigma with many questions that remain unanswered. The ability of the pathogen to survive and switch between varied physiological states necessitates a protracted therapeutic regimen that exerts an excessive strain on low-resource countries. To complicate things further, there has been a significant rise of antimicrobial resistance. Existing control measures, including treatment regimens have remained fairly uniform globally for at least half a century and require reinvention. Overcoming the societal and scientific challenges requires an increase in dialog to identify key regions that need attention and effective partners with whom successful collaborations can be fostered. In this report, we explore the discussions held at the International TB Summit 2015 hosted by EuroSciCon, which served as an excellent platform for researchers to share their recent findings. Ground-breaking results require outreach to affect policy design, governance and control of the disease. Hence, we feel it is important that meetings such as these reach a wider, global audience.